2021
DOI: 10.1002/cnm.3462
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics of the airways after left‐upper pulmonary lobectomy: A case study

Abstract: Pulmonary lobectomy is the gold standard intervention for lung cancer removal and consists of the complete resection of the affected lung lobe, which, coupled with the re-adaptation of the remaining thoracic structures, decreases the postoperative pulmonary function of the patient. Current clinical practice, based on spirometry and cardiopulmonary exercise tests, does not consider local changes, providing an average at-the-mouth estimation of residual functionality. Computational Fluid Dynamics (CFD) has prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
(270 reference statements)
6
4
0
Order By: Relevance
“…These fluid dynamic alterations are derived from the resection of an entire lung lobe and the geometrical adaptation of the remaining structures, especially for upper lobe lobectomies. Limited to LUL lobectomies, our results are consistent with the two previous studies characterizing this type of lobectomy 23 , 24 . With respect to Gu et al 23 , relatively higher variations of fluid dynamic parameters are observed in our cohort of patients that underwent LUL lobectomy, although this can be possibly ascribed to the higher inlet flow rate considered in the simulations of the presented work.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These fluid dynamic alterations are derived from the resection of an entire lung lobe and the geometrical adaptation of the remaining structures, especially for upper lobe lobectomies. Limited to LUL lobectomies, our results are consistent with the two previous studies characterizing this type of lobectomy 23 , 24 . With respect to Gu et al 23 , relatively higher variations of fluid dynamic parameters are observed in our cohort of patients that underwent LUL lobectomy, although this can be possibly ascribed to the higher inlet flow rate considered in the simulations of the presented work.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to Gu et al 23 , relatively higher variations of fluid dynamic parameters are observed in our cohort of patients that underwent LUL lobectomy, although this can be possibly ascribed to the higher inlet flow rate considered in the simulations of the presented work. The obtained values are indeed in line with Tullio et al 24 , who considered the same inlet flow of the presented study. For upper lobes lobectomies, the increment of pressure, velocity, and wall shear stress can be associated with the severe bronchial stenosis observed and the general re-adaptation of the remaining lower lobes.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations